Chinese communication studies : contexts and comparisons - Lu, Xing, 1956-; Jia, Wenshan, 1961-; Heisey, D. Ray (Advances in communication and culture., 2002)
Many varying factors contribute to the dynamics of Chinese communication, which both resembles and differs from its Western counterparts. In this provocative new collection of essays, an international group of scholars challenges the conventional notion of Chinese culture as static, recognizing the causes of cultural change and strategies of resistance. Examining communication contexts in mainland China, Hong Kong, and Taiwan, and comparing them to those of the United States and Europe, Chinese Communication Studies: Context and Comparisons considers the relationship between culture and communication in Chinese political, gender, family, and media contexts, providing the reader with insight both into how enduring Chinese cultural values are, and how they are being appropriated to meet political and economic goals.